2014
DOI: 10.1292/jvms.14-0026
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Composition of Epithelial Cells in Follicle-Associated Intestinal Crypts of Peyer’s Patches in the Rat Small Intestine

Abstract: The epithelial cell composition was investigated in the follicle-associated intestinal crypt (FAIC) of rat Peyer’s patches. The epithelium of the FAIC mainly consisted of columnar epithelial cells, goblet cells and Paneth cells. The characteristics of secretory granules in Paneth cells and goblet cells of both the FAIC and ordinary intestinal crypts (IC) were almost the same in periodic acid-Schiff (PAS) reaction, Alcian blue (AB) staining and the immunohistochemical detection of lysozymes and soluble phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In the present study, TLR-2 was detected in the MV in both FAIV and IV, but almost all MV of FAE were negative for TLR-2. Considering the previous finding suggesting that indigenous bacteria adhered more frequently to FAE than to epithelia of FAIV and IV [17], these findings suggest that FAE might provide the circumstances where indigenous bacteria more easily adhere and proliferate before their settlement by the near complete absence of TLR-2 expression. Furthermore, the level of TLR-2 expression in MV was lower in the epithelium of f-FAIV than in the epithelia of IV and af-FAIV.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In the present study, TLR-2 was detected in the MV in both FAIV and IV, but almost all MV of FAE were negative for TLR-2. Considering the previous finding suggesting that indigenous bacteria adhered more frequently to FAE than to epithelia of FAIV and IV [17], these findings suggest that FAE might provide the circumstances where indigenous bacteria more easily adhere and proliferate before their settlement by the near complete absence of TLR-2 expression. Furthermore, the level of TLR-2 expression in MV was lower in the epithelium of f-FAIV than in the epithelia of IV and af-FAIV.…”
Section: Discussionsupporting
confidence: 62%
“…Indigenous bacteria more frequently adhere to FAE than to epithelia of FAIV and IV [13, 17, 20]. In the rat small intestine, it is suggested that bacteria proliferating on the mucosal surface are recognized by TLR-2 expressed in MV of IV and that TLR-2-negative MV at the apices of IV probably contribute to the adhesion of indigenous bacteria at the villous apices [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations